Community Health Partnerships for Chronic Disease Prevention Among Latinos: The San Diego Prevention Research Center - Elder, John P. (J Prim Prev, 2013)
Over 20 years ago, university–community partnerships (i.e., Prevention Research Centers [PRCs]) across the United States were funded by the Centers for Disease Control and Prevention to conduct research and training in order to promote health and prevent disease in underserved populations. In 2004, the San Diego PRC (SDPRC) became the first PRC to focus on obesity prevention and control in a community of mostly Mexican Americans/Mexican immigrants. The SDPRC was also the first PRC to comprise a university–community partnership with a school of public health, a school of medicine, and a federally qualified health center. In conjunction with two additional funded community partners and involvement of a community advisory board, the SDPRC seeks to develop effective intervention strategies that ultimately lead to behavior change. Now in its second cycle of funding, the SDPRC has identified three primary principles that are important for these and similar efforts: (1) developing culturally appropriate interventions requires community engagement; (2) building the evidence in a systematic and rigorous way yields meaningful strategies for translation to practice; and (3) translating evidence-based interventions to practice involves capacity building for both researchers and community partners. This article describes these principles to help others involved in similar intervention efforts identify the best approach for promoting health in their own communities.